Analisis Faktor-Faktor yang Mempengaruhi Penyerapan Tenaga Kerja dan Produktivitas Kerja Patung Kayu - Arissana Yeni, Nyoman Triani; Sri Budhi, Made Kembar (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2016)
The purpose of this research is to analyze and determine the direct effect of capital, wages and technology on employment, the direct effect of capital, wages, technology and employment on work productivity, the indirect effect of capital, wages and technology to work productivity through absorption labor. This research was conducted in Badung with employers respondents wooden sculptures which includes the District 6 is Abiansemal, Kuta, Kuta Utara, South Kuta, Mengwi and evening. Object of the study include capital, wages and technology. The sampling technique used is Proporsionate Stratified Random Sampling. Samples of this research were 111 respondents. The data collected by observation, interviews and questionnaires. Data processed uses path analysis techniques to analyze the effect of the direct path between the variables with other variables and test Sobel analyze the effect of indirectly through intervening variables.. The results showed capital, wages and technology and significant positive effect on employment wooden sculptures.
Keywords: Capital; Wage Rates; Technology; Absorption of Labor; Work Productivity